Women’s Character Education and Gender Equality in Indonesia: A Pancasila-Based Ethical Analysis - Riskawati Riskawati; Fediyatun Muntazarah (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2026)
Study of education character and gender equality in Indonesia in general focused on expansion access education and participation women, but not yet in a way adequate analyze How education character reproduce or challenge relation gender power in framework Pancasila values. The gap This show the need analysis ethics that places Pancasila not just as a normative slogan, but as framework evaluative critical. This article aim analyze in a way conceptual relation between education character women and gender equality in Indonesia through perspective Pancasila ethics. Research This use approach qualitative with design analysis conceptual based studies literature to journal scientific accredited, literature international reputable, and books relevant academic​ with education character, gender studies, and Pancasila philosophy. Analysis done in a way thematic with emphasize the principle just and civilized humanity​ as well as justice social. Study results show that education character Woman Still tend normative and adaptation oriented social, so that potential maintain double moral standards and limitations agency women. This article contribute to clarification theoretical about the position of Pancasila as framework ethical critical for reconstruct education more characters​ equal. The implications, policies and practices education need directed at an empowering and gender equitable approach.